5v-8v-3v-6=

Simple and best practice solution for 5v-8v-3v-6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5v-8v-3v-6= equation:


5v-8v-3v-6=0

We simplify the equation to the form, which is simple to understand
5v-8v-3v-6=0

We move all terms containing v to the left and all other terms to the right.
+5v-8v-3v=0+6

We simplify left and right side of the equation.
-6v=+6

We divide both sides of the equation by -6 to get v.
v=-1

See similar equations:

| 18=p-6 | | ax+2=2y | | x+x+x+12+5*x=10*x-2 | | (3x^5/85^4)^-3 | | 9.5/1.25 | | 126-3(6x-6)= | | 4c+6=5c-9 | | 4x^2-76=3x | | 2x2y0(5xy2)2/5(-2xy2) | | 4x^2-7=-27x | | 5f+3= | | 5p=p-6 | | y=177-8x | | 4(4y+9)=50 | | 3a+10=a+38 | | 24x^2+22x+3=0 | | 4(x-1)-3=13 | | 8-18x=2-x | | 2-3(-9)=-7 | | 19.45=-8.6r+-12.8 | | 4t-8+14t=3-4t-11 | | 3v+19=5v-17 | | 2-3(5)=-7 | | 12s+20=17s | | 19a-8=15a | | 4/5-(-16/5) | | -5(8a-6)=-34-8 | | 2z+20=3z-9 | | 3p+13=p+15 | | p=5.65-.05(78.4) | | 328=8(6+5a) | | 5w-14=4w+4 |

Equations solver categories